2016
DOI: 10.1111/jai.13118
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal histomorphology, autochthonous microbiota and growth performance of the oscar (Astronotus ocellatusAgassiz, 1831) following dietary administration of xylooligosaccharide

Abstract: The present study investigates the changes in intestinal histomorphology, autochthonous microbiota and growth performance of the oscar, Astronotus ocellatus, following dietary administration of different levels of xylooligosaccharide (XOS). One hundred forty-four oscars (8.88 AE 0.23 g; n = 144) were randomly stocked in 12 aquaria (100-L) assigned to four treatments repeated in triplicate. Fish were fed a commercial diet, Biomar, supplemented with different levels (0 [control], 0.5, 1, 2%) of XOS for 8 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 28 publications
1
9
2
Order By: Relevance
“…However, in contrast to our results, growth‐enhancing effects of dietary XOS have been reported previously in other fish species such as turbot ( Scophthalmus maximus ) by Li, Wang, Wang, and Jiang (), crucian carp ( Carassius auratus gibelio ) by Xu, Wang, Li, and Lin () and oscar ( Astronotus ocellatus ) by Hoseinifar, Khalili, et al. (). Moreover, Hoseinifar, Ahmadi, et al.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to our results, growth‐enhancing effects of dietary XOS have been reported previously in other fish species such as turbot ( Scophthalmus maximus ) by Li, Wang, Wang, and Jiang (), crucian carp ( Carassius auratus gibelio ) by Xu, Wang, Li, and Lin () and oscar ( Astronotus ocellatus ) by Hoseinifar, Khalili, et al. (). Moreover, Hoseinifar, Ahmadi, et al.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results Xu et al. () reported that administration of 50–200 mg/kg XOS in crucian carp, 10–30g/kg FOS in the diet of Caspian roach (Soleimani et al., ) and 10g/kg sc‐FOS in the diet of common carp (Hoseinifar, Eshaghzadeh, et al., ; Hoseinifar, Khalili, et al., ; Hoseinifar, Zoheiri, et al., ) had significant effects on amylase, lipase and protease activities compared to the control group. Digestive enzymes activities were unaffected by addition of XOS to diet of sobaity seabream fish.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…2010b; Hoseinifar et al . 2011b, , ,b, ,b; Azimirad et al . ) and that SCFA production change depending on the prebiotics provided (Kihara & Sakata ; Burr et al .…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…; Hoseinifar et al . 2015a, 2016c; Carbone & Faggio ; Dawood & Koshio ), none has made a general review of prebiotics’ benefits and possible mechanisms of action. Thus, the aim of this review is to fulfil this gap, providing data on prebiotics’ benefits and mechanisms of action, with special attention to effects on growth performance, gut microbiota, digestive enzymes, gut morphology, immune response, disease and stress resistance, intermediary metabolism, and oxidative status.…”
Section: Introductionmentioning
confidence: 99%